Batch Production of Trimethylolpropane Ester From Palm Oil as Lubricant Basestock - Sulaiman, Siti Zubaidah (2006)
The batch production of trimethylolpropane ester from palm oil as lubricant basestock was performed in 10 liters mini pilot batch reactor incorporated with high vacuum pump. This study has examined the optimum operating conditions in order to obtain the maximum level of production yield in a minimum time or minimum cost. The experiments were carried out to synthesize palm oil based trimethylolpropane ester via chemical reactions in batch mode. The experiments focused on the effects of variations in the 1) temperature, 2) vacuum pressure, 3) molar ratio, 4) amount of catalyst and 5) speed of agitation. The chemical compositions of samples were analyzed via gas chromatography. The final products were tested for their lubrication properties such as TAN (Total Acid Number), kinematic viscosity, viscosity index (VI), wear and friction test. Approximately 5 liters of trimethylolpropane ester from palm oil containing 86 w/w% of triester was successfully synthesized in two hours of operation. The optimal reaction conditions for mini pilot batch reactor were found to be as follows; 1) temperature: 120°C, 2) pressure: 20 mbar, 3) molar ratio: 3.8:l (POME to TMP), 4) catalyst: 0.9 w/w% 5) speed of agitation: 180 rpm. The kinetics data obtained from the laboratory scale experiment was successfully applied to the mini pilot batch reactor to estimate the yield of triester. As a conclusion, the study has proven that the synthesis method to produce trimethylolpropane ester from palm oil as a lubricant basestock developed in the laboratory (one liter) can be scale up to a mini pilot batch reactor (10 liters) with marginal effect on the reaction yield.